P788 Significant medical and surgical morbidity in perianal Crohn's disease: Results from a population-based study. (16th January 2018) - Mak, W Y; Mak, O S; Lee, C K; Tang, W; Leung, W K; Li, M K K; Lo, F H; Wong, M T; Sze, A S F; Leung, C M; Tsang, S W C; Shan, E H S; et al.
Abstract: Background: The presence of perianal fistulas denotes a distinct and more aggressive disease course in patients with Crohn's disease (CD). We studied the epidemiology and clinical outcomes of patients with perianal CD using data from a prospectively collected population-based IBD registry in Hong Kong. Methods: Consecutive patients with perianal CD (PCD) were identified from the Hong Kong IBD registry which covers 13 public hospitals in Hong Kong. Disease characteristics, fistula subtypes, treatment and clinical outcomes including need for surgery and mortality were analysed. Risks for medical and surgical therapies were assessed using Kaplan–Meier analysis. Results: Among 994 patients with CD, 283 (28.5%) had perianal involvement. The mean age at diagnosis of PCD was 29.1 years old (±12.7) and 78.8% were male. Median follow-up duration was 106 months (IQR: 65–161 months). One hundred and twenty patients (42.4%) presented with perianal involvement at diagnosis of CD. Perianal fistula was the most common (84.8%), followed by perianal abscess (52.7%), anal fissures (6.7%), anal stricture (6.4%) and rectovaginal fistula (4.2%). Among the 242 patients with perianal fistulas, 70 patients (29.2%) required more than 5 courses of antibiotics and 98 (40.5%) had at least 2 surgical procedures for perianal fistulas. Nine patients required defunctioning surgery (3 ileostomy and 6 colostomy) and 4 required proctectomy. Eighty-four patients (34.7%) received biologics for treatment of PCD (67 Infliximab, 16 adalimumab and 1 vedolizumab). Forty-one patients (48.8%) stopped biologics after a median of 84 months (IQR 6–41 months). Eleven of them (26.8%) required repeated courses of biologics. Cumulative probabilities for use of biologics were 4.7% at 12 months, 5.8% at 36 months and 8.6% at 96 months while cumulative probabilities for surgery were 88.5% at 12 months, 94% at 36 months and 99% at 96 months. Five patients succumbed within the reviewed period. Two died of anal cancer, two died of CD-related complications and one died of pneumonia. Conclusions: Outcome of Chinese patients with PCD is poor. Over 40% of patients had PCD at diagnosis. Patients developed PCD at a very young age and often required multiple courses of antibiotics and surgery.